2018
DOI: 10.1007/s11284-018-1569-1
|View full text |Cite
|
Sign up to set email alerts
|

Nickel hyperaccumulation by Streptanthus polygaloides is associated with herbivory tolerance

Abstract: Metal hyperaccumulation can increase plant resistance to herbivory, but tolerance as an herbivore defense has been little investigated. This study explored the interaction between Ni hyperaccumulation and herbivory tolerance using Streptanthus polygaloides. Plants were grown in one of two potting soil Ni treatments: Ni‐amended (800 µg g−1 added Ni) or unamended (0 µg g−1 added Ni). One‐month‐old plants were arbitrarily assigned one of four levels of artificial herbivory damage applied to the leaves. Response v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
0
0
Order By: Relevance
“…Kazemi‐Dinan et al (2015) performed a common garden experiment that supports the idea that Cd and Zn hyperaccumulation can reduce herbivore attack and improve the performance of Arabidopsis halleri (L.) O'Kane and Al‐Shehbaz. Several other studies (Ghasemi et al, 2014; Isnard et al, 2020; Meindl & Ashman, 2017; Mincey et al, 2018) also suggest that a hyperaccumulated element improves growth or reproductive potential of a hyperaccumulator. Our study's results are in accord with the “elemental stimulation” hypothesis, as Ni enhanced root growth and stimulated lateral root production occurred in S. polygaloides .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Kazemi‐Dinan et al (2015) performed a common garden experiment that supports the idea that Cd and Zn hyperaccumulation can reduce herbivore attack and improve the performance of Arabidopsis halleri (L.) O'Kane and Al‐Shehbaz. Several other studies (Ghasemi et al, 2014; Isnard et al, 2020; Meindl & Ashman, 2017; Mincey et al, 2018) also suggest that a hyperaccumulated element improves growth or reproductive potential of a hyperaccumulator. Our study's results are in accord with the “elemental stimulation” hypothesis, as Ni enhanced root growth and stimulated lateral root production occurred in S. polygaloides .…”
Section: Discussionmentioning
confidence: 91%
“…It is the only species of the genus that hyperaccumulates Ni (Kruckeberg & Reeves, 1995; Reeves et al, 1981). It is also the most‐investigated North American Ni hyperaccumulator, as it has been the subject of studies of morphology, ecology, genetics, herbivore interactions, and elemental concentration (e.g., Boyd et al, 2000, 2009; Davis et al, 2001; Jhee et al, 2006; Mincey et al, 2018; Mincey & Boyd, 2018; Pope et al, 2013). Streptanthus insignis Jeps.…”
Section: Introductionmentioning
confidence: 99%
“…Inoue et al (2024) studied a rare species ( Saussurea ochiaiana ) from Japan and showed that habitat conditions suitable for the regeneration of this species are decreasing because of climate change and the depopulation of rural communities, implying that urgent conservation strategies are needed. Mincey and Boyd (2024) report on root foraging by the Ni hyperaccumulator Streptanthus polygaloides from the United States and found that it exhibited positive root foraging responses which they termed “nickelophilic root foraging.” Their findings suggest that Ni hyperaccumulation has adaptive value, as opposed to the nonadaptive “inadvertent uptake” hypothesis that was listed by Boyd and Martens (1992) as a potential explanation for hyperaccumulation in a seminal paper published in the proceedings of the 1st ICSE (held in Davis, California, USA) and updated by Boyd (2014). Sherri et al (2024) investigated the effect of polycyclic aromatic hydrocarbons and trace elements on antioxidant response and phytoextraction efficiency in Noccaea caerulescens .…”
Section: This Special Issue Of Ecological Researchmentioning
confidence: 99%